Prevalence of proximate risk factors of active tuberculosis in latent tuberculosis infection: A cross-sectional study from South India - Munisankar, Saravanan; Rajamanickam, Anuradha; Balasubramanian, Suganthi; Muthusamy, Satishwaran; Menon, Pradeep Aravindan; Ahamed, Shaik Fayaz; Whalen, Christopher; Gumne, Paschaline; Kaur, Inderdeep; Nadimpalli, Varma; Deverakonda, Akshay; Chen, Zhenhao; et al. (Frontiers in Public Health, 2022)
The prevalence of proximate risk factors for active tuberculosis (TB) in areas of high prevalence of latent tuberculosis infection (LTBI) is not clearly understood. We aimed at assessing the prevalence of non-communicable multi-morbidity focusing on diabetes mellitus (DM), malnutrition, and hypertension (HTN) as common risk factors of LTBI progressing to active TB. In a cross-sectional study, 2,351 adults (45% male and 55% female) from villages in the Kancheepuram district of South India were enrolled between 2013 and 2020. DM was defined as HbA1c >6.4%, undernutrition was defined as low body mass index (LBMI) <18.5 kg/m2, obesity was classified as BMI ≥25 kg/m2, HTN was reported as systolic pressure >130 mmHg, and LTBI was defined as positive (≥ 0.35 international units/ml) by QuantiFERON Gold In-Tube assay. A total of 1,226 individuals (52%) were positive for LTBI out of 2351 tested individuals. The prevalence of DM and pre-diabetes mellitus (PDM) was 21 and 35%, respectively, HTN was 15% in latent tuberculosis (LTB)-infected individuals. The association of DM [odds ratio (OR)]; adjusted odds ratio (aOR) (OR = 1.26, 95% CI: 1.13–1.65; aOR = 1.19, 95% CI: 1.10–1.58), PDM (OR = 1.11, 95% CI: 1.0–1.35), and HTN (OR = 1.28, 95% CI: 1.11–1.62; aOR = 1.18, 95% CI: 1.0–1.56) poses as risk factors of LTBI progression to active TB. The prevalence of LBMI 9% (OR = 1.07, 95% CI: 0.78–1.48) and obesity 42% (OR = 0.85, 95% CI: 0.70–1.03) did not show any statistically significant association with LTB-infected individuals. The present evidence of a high burden of multi-morbidity suggests that proximate risk factors of active TB in LTBI can be managed by nutrition and lifestyle modification.